Floof Disaster Management Strategy In Sidoarjo District Based On SWOT Analysis - Nanda Bayu Saputra; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze and describe flood disaster management strategies in Sidoarjo Regency based on a SWOT analysis. The method used is descriptive qualitative, the technique of determining the informants used is purposive sampling. The types of data obtained are primary data and secondary data obtained through data collection through observation, interviews and documentation. Furthermore, data analysis was carried out using Milles and Huberman data analysis methods and SWOT analysis. The results of this study obtained the SO strategy the need for technology-based innovation specifically in flood disaster management. WO Strategy Cooperating with the private sector and academics in the development of infrastructure and apparatus in flood prevention. ST strategy the need for education programs to the public to be aware of disasters and participate in flood management and disaster studies and WT strategies The need for a coalition of actors including the government, private, community, and academic sectors in creating regulations related to flood management programs.